2021
DOI: 10.1186/s13024-021-00434-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing GABAergic signaling ameliorates aberrant gamma oscillations of olfactory bulb in AD mouse models

Abstract: Background Before the deposition of amyloid-beta plaques and the onset of learning memory deficits, patients with Alzheimer’s disease (AD) experience olfactory dysfunction, typified by a reduced ability to detect, discriminate, and identify odors. Rodent models of AD, such as the Tg2576 and APP/PS1 mice, also display impaired olfaction, accompanied by aberrant in vivo or in vitro gamma rhythms in the olfactory pathway. However, the mechanistic relationships between the electrophysiological, bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 120 publications
(112 reference statements)
1
37
0
Order By: Relevance
“…We next evaluated ACC-HIPP connectivity in the frequency domain ( Figure 5E ) by coherence analysis ( Chen et al, 2021 ), and observed significantly increased coherence in the gamma range in model rats ( Figure 5F ). To better understand the connectivity in more precise phase ranges, we next used WPLI analysis ( Vinck et al, 2011 ) which can reduce the contingency caused by the bidirectional connection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next evaluated ACC-HIPP connectivity in the frequency domain ( Figure 5E ) by coherence analysis ( Chen et al, 2021 ), and observed significantly increased coherence in the gamma range in model rats ( Figure 5F ). To better understand the connectivity in more precise phase ranges, we next used WPLI analysis ( Vinck et al, 2011 ) which can reduce the contingency caused by the bidirectional connection.…”
Section: Resultsmentioning
confidence: 99%
“…Recent animal and human studies provide converging evidence that gamma oscillations are closely related to pain perception ( Hu and Iannetti, 2019 ; Tan et al, 2019 ). In addition, cross-frequency phase-amplitude coupling (PAC), in which the amplitude of higher (e.g., gamma) rhythms is particularly modulated by the phase of lower (e.g., theta) rhythms, indicates a more complex regulatory feature through interactions between different frequency bands, such as long-range theta and local gamma communication ( Wirt and Hyman, 2019 ; Chen et al, 2021 ). However, the possible abnormalities induced by PDM in ACC-HIPP connectivity and the underlying mechanisms of the condition remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…W. Li et al and Chen et al measured OB activity in mice expressing amyloid precursor protein and presenilin 1 (APP/PS1) and found significant increases in gamma band power associated with synaptic deficits [18, 19]. Both groups found that treatment with a GABA agonist decreased the heightened gamma power, suggesting that increases in the gamma band may have been due to a decrease in GABA-induced inhibition to the MCs.…”
Section: Discussionmentioning
confidence: 99%
“…While they also found an increase in gamma power and impaired synaptic function, MC firing rates were decreased rather than elevated, suggesting other mechanisms at play. Note also that because AD-like pathology was induced by gene expression in all of these studies [1821], it is more relevant to the FD modeled here rather than to SD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation